Preeclampsia / eclampsia:challenge for obstetrician-Gynecologist - Pacheco, José (2006)
The uterus to placenta blood flow reduction would be the initial factor for preeclampsia, secondary to anomalous spiral uterine arteries invasion by the extravillous cytotrophoblastic cells, associated to both vascular tonus and immunologic and inflammatory balance local alterations, sometimes with genetic predisposition. There is endothelial cell dysfunction, dyslipidemia (especially hypertriglyceridemia), hyperinsulinemia, hyperleptinemia, antioxidant-prooxidant imbalance. Preeclampsia is an early pregnancy disease characterized by hypertension and proteinuria, expressed late in pregnancy. We still do not have a clinical useful test to predict preeclampsia. Combining both placental insufficiency and endothelial markers and PlGF y sFlT-1 serum or urinary levels in the first trimester is promising. Personal and familiar hypertension history is extremely important. Pregnant women with arterial hypertension should be attended in specialized centers. The antihypertensive therapy has little effect on pregnancy outcome. We suggest the use of low doses of aspirin in women with previous early preeclampsia. Calcium channel blockers are very useful in treating acute hypertension. Preeclampsia treatment consists in the birth of both fetus and placenta, the time determined by maternal and fetal conditions.